Political economy of the Nice treaty: Rebalancing the EU Council / The Future of European Agricultural Policies - Frédéric Bobay; Winfried von Urff (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
Contents: 1 - Jürgen von Hagen, Jean Pisani-Ferry - Forum Economique Franco-Allemand /Deutsch-Französisches Wirtschaftspolitisches Forum – 4 - Frédéric Bobay - Political Economy of the Nice Treaty: Rebalancing the EU Council – 21 - Winfried von Urff - The Future of European Agricultural Policies
Keywords: 330; Regierung; Abstimmungsregel; Europäische Integration; EU-Staaten; Shapley-Wert